1981
DOI: 10.1002/ana.410090303
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of criteria used for localizing epileptic foci in patients considered for surgical therapy of epilepsy

Abstract: Criteria for anterior temporal lobectomy, performed on seven patients with partial complex seizures, were derived from a battery of fourteen presurgical tests. Seven tests were routine studies aimed at identifying a focus of epileptic excitability, while seven were designed to reveal areas of focal functional deficit. Conflicting information was frequently obtained from the tests of epileptic excitability, suggesting that it is probably inaccurate to view patients with partial complex seizures as having a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
2
2

Year Published

1982
1982
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(115 citation statements)
references
References 33 publications
9
102
2
2
Order By: Relevance
“…According to several authors, [14][15][16][17][18][19][20] dendritic and neuronal losses are always present in epileptic patients. These losses are independent of crisis type, and if we consider the anatomical and histopathological disorders responsible for poor performance by epileptic patients in the auditory skills evaluated in the SSW test, these authors' findings would explain such performance observed in both groups of epileptic patients studied here.…”
Section: Discussionmentioning
confidence: 99%
“…According to several authors, [14][15][16][17][18][19][20] dendritic and neuronal losses are always present in epileptic patients. These losses are independent of crisis type, and if we consider the anatomical and histopathological disorders responsible for poor performance by epileptic patients in the auditory skills evaluated in the SSW test, these authors' findings would explain such performance observed in both groups of epileptic patients studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in intact animal models (Engel and Ackerman 1980;Gotman 1984) and human studies (Engel et al 1981;Gotman and Marciani 1985) interictal electroencephalographic (EEG) spiking does not always correlate with seizure frequency or severity. The absence of interictal activity during low-Ca 2ϩ , zero-Mg 2ϩ plus Cd 2ϩ , and zero-Mg 2ϩ plus veratridine bursting is consistent with these findings.…”
Section: Nonsynaptic Nature Of Ictal Epileptiform Activitymentioning
confidence: 99%
“…The human ␤1 subunit prolongs neuronal depolarization when co-expressed in vitro with a rat brain sodium channel ␣ subunit RBII. Point mutations in the voltage-sensor regions of the sodium channel ␣-subunit SCN1A have been associated with seizures in two families (Escayg et al 2000). Another candidate gene for epilepsy, the SCN5A sodium channel (previously thought to be expressed only in heart tissue) is selectively expressed in only the limbic system of the brain (Hartmann et al 1999).…”
Section: Sodium Channel Defects Relevance To Seizures In Vivomentioning
confidence: 99%
“…Huntington's disease patients who demonstrated dementia have been studied by the same methods (Kuhl et al ., 1981. While these patients con sistently demonstrated profound striatal hypo metabolism, they typically had preserved cortical metabolic rates (Fig.…”
Section: Dementiamentioning
confidence: 99%